Comparison of mechanical removal of perennial ryegrass overseeding out of bermudagrass to chemical transitions. Issue 1 (5th February 2021) - Dickson, K. H.; Segars, C. A.; Sorochan, J. C.; Moss, J. Quetone; Harris, D.; Strunk, W. D.
Abstract: In the fall, bermudagrass athletic fields are overseeded with perennial ryegrass [ Lolium perenne L.] to provide a uniform playing surface to slowed or dormant bermudagrass. Chemical techniques have been utilized for quick and efficient spring transition of perennial ryegrass. Fraise mowing has been identified as a tool that can aid in ryegrass transition in the spring. These studies were to determine the effectiveness of spring transition comparing mechanical removal of perennial ryegrass overseeding to traditional techniques on 'Riviera' bermudagrass [C ynodon dactylon (L.) Pers.]. In 2017, field studies were conducted at the University of Tennessee Center for Athletic Field Safety (Knoxville, TN) and the Oklahoma State University Turfgrass Research Center (Stillwater, OK). The seven treatments for the study were: fraise mow at 6.4 mm from the grass surface, fraise mow at 12.7 mm from the grass surface, fraise mow at 19.1 mm from the grass surface, spray application of trifloxysulfuron at the 27.8 g ha −1 with non‐ionic surfactant at 0.25% v/v, spray application of foramsulfuron at the 28.9 g ha −1, scalping (19.1 mm) with a rotatory mower, and an untreated control. Treatments were initiated on 11 May 2017 in Stillwater, OK USA and 17 May 2017 in Knoxville, TN USA. Plots were monitored for six weeks following treatment application. Fraise mowing at 12.7 mm was identified as the optimum depth for perennial ryegrass transitioning in this study compared to chemical transitions. This study found that the fraise mowing at 12.7 mm removed more perennial ryegrass and maintained percent green turfgrass cover throughout the study. However, if time of use for the turfgrass area is not a primary concern then depths greater than 12.7 mm are effective at perennial ryegrass removal but delay spring green‐up.